Lr34/Yr18/Sr57/Pm38 confers broad-spectrum resistance to fungal diseases via transport of sinapyl alcohol for cell wall lignification in wheat - Yichen Zhang; Guang Chen; Yiming Zang; Bhavani, Sridhar; Bin Bai; Wei Liu; Miaomiao Zhao; Yikeng Cheng; Shunda Li; Wei Chen; Wenhao Yan; Hailiang Mao; et al. (Elsevier, 2024)
The widely recognized pleiotropic adult plant resistance gene Lr34 encodes an ATP-binding cassette transporter and plays an important role in breeding wheat for enhanced resistance to multiple fungal diseases. Despite its significance, the mechanisms underlying Lr34-mediated pathogen defense remain largely unknown. Our study demonstrates that wheat lines carrying the Lr34res allele exhibit thicker cell walls and enhanced resistance to fungal penetration compared to those without Lr34res. Transcriptome and metabolite profiling revealed that the lignin biosynthetic pathway is suppressed in lr34 mutants, indicating a disruption in cell wall lignification. Additionally, we discovered that lr34 mutant lines are hypersensitive to sinapyl alcohol, a major monolignol crucial for cell wall lignification. Yeast accumulation and efflux assays confirmed that the LR34 protein functions as a sinapyl alcohol transporter. Both genetic and virus-induced gene silencing experiments demonstrated that the disease resistance conferred by Lr34 can be enhanced by incorporating the TaCOMT-3B gene, which is responsible for the biosynthesis of sinapyl alcohol. Collectively, our findings provide novel insights into the role of Lr34 in disease resistance through mediating sinapyl alcohol transport and cell wall deposition, and highlight the synergistic effect of TaCOMT-3B and Lr34 against multiple fungal pathogens by mediating cell wall lignification in adult wheat plants.